Impact of Performance Appraisal on Organizational Citizenship Behaviour and Intention to Stay through Affective Commitment: A Literature Review - R. K., Ravikumar; Raya, Dr. R. P. (International Journal of Scientific Research and Management (IJSRM), 2019)
The purpose of this paper is to develop theoretical framework linking performance appraisal, affective commitment, intention to stay, and organizational citizenship behaviour. The social exchange and procedural justice theories applied to link performance appraisal with affective commitment, intention to stay, and organizational citizenship behaviour. Propositions were framed based on the in-depth literature review and tested the propositions based on the previous similar findings. This study will provide platform to conduct empirical study to examine the impact of performance appraisal on affective commitment, intention to stay, and organizational citizenship behaviour.